SCIPA Com: outcomes from the spinal cord injury and physical activity in the community intervention. - de Oliveira, B.; Howie, E.; Dunlop, S.; Galea, M.; McManus, Alexandra; Allison, G. (2016)
Study design: Quasi-experimental translational study with pre- and post-measures. Objectives: To determine the effects of the Spinal Cord Injury and Physical Activity in the Community (SCIPA Com) intervention on leisure-time physical activity (LTPA) and associated outcomes among participants with spinal cord injury (SCI). Setting: Young Men’s Christian Associations and community fitness centers, Australia and New Zealand. Methods: SCIPA Com consisted of three stages: (i) training exercise professionals via the Train the Trainers Spinal Cord Injury course; (ii) implementation of supervised physical activity programs twice a week for 30 to 60 min for 8 to 12 weeks; and (iii) follow-up assessments on health outcomes over 9 months. Participants with SCI were classified as active or inactive by baseline LTPA levels and linear mixed methods compared LTPA between groups over time. Results: Sixty-four community-dwelling participants with SCI completed customized physical activity programs. Compared with baseline, there were significant improvements in LTPA (26 min per day, 95% confidence interval (CI): 16.6–35.4; P<0.001), functional goals (2, 95% CI: 1.72–2.37; P<0.001), self-esteem (1.5, 95% CI: 0.72–2.27; P<0.001) and overall quality of life (P<0.05). Over time, LTPA participation was greater among the active compared with the inactive group, although LTPA levels among the inactive improved compared with baseline. Conclusions: Significant improvements in LTPA participation and health outcomes were observed, especially among inactive individuals with SCI. SCIPA Com is an ecologically valid intervention based on training and support provided to community exercise professionals who, although new to adapted training, delivered effective physical activity programs for those at risk of inactivity.